Standby citizens: diverse faces of political passivity. (17th June 2013) - Amnå, Erik; Ekman, Joakim
<x content-type="archive" xml:space="preserve">Abstract</x> The current debate on political participation is bound to a discussion about whether citizens are active or passive. This dichotomous notion is nurtured by an extensive normative debate concerning whether passivity is an asset or a threat to democracy; and it is especially manifest in studies of young people's political orientations. Drawing on this discussion, the present study goes beyond the dichotomy by keeping political interest conceptually separate from participation in order to improve our understanding of political passivity. Multivariate cluster analysis of empirical data on Swedish youth suggests that we need to consider three distinctive forms of 'political passivity'. In the paper we present empirical evidence not only of the existence of a particular 'standby citizen', but also of two kinds of genuinely passive young people: unengaged and disillusioned citizens. Alongside active citizens, these people are in distinctly different categories with regard to their political behavior. This entails a new analytical framework that may be used to analyze an empirical phenomenon that has received surprisingly little attention in the literature on political participation and civic engagement.